The Effect of the Human Development Index (HDI) and the Provincial Minimum Wage (PMW) on the Percentage of Poor Population in North Sumatra during the 2018–2025 Period - Yehezkiel Exaudi Banjarnahor; Fais Irawan; Kevin Lejon Simamora (Outline Publisher, 2026)
Human Development Index (HDI), Minimum Wage, Poverty, North Sumatra, Multiple Linear Regression. Poverty is one of the main problems in economic development that is still faced by various regions in Indonesia, including North Sumatra Province. This study aims to analyze the effect of the Human Development Index (HDI) and the Provincial Minimum Wage (PMW) on the Percentage of Poor Population in North Sumatra during the period 2018-2025. This research uses a quantitative approach by utilizing secondary data obtained from official publications of the Central Statistics Agency. The analytical method used is multiple linear regression with the assistance of SPSS version 25 software. Before conducting regression analysis, the data were first tested through classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results show that partially the Human Development Index has a negative and significant effect on the percentage of poor population with a t-value of -3.174 and a significance level of 0.025. The Provincial Minimum Wage also has a negative and significant effect on the percentage of poor population with a t-value of -10.178 and a significance level of 0.000. Simultaneously, the Human Development Index and Provincial Minimum Wage have a significant effect on the percentage of poor population with an F-value of 62.130. The coefficient of determination value of 0.961 indicates that 96.1% of the variation in the percentage of poor population can be explained by these two variables. These findings indicate that improving the quality of human development and implementing appropriate minimum wage policies can contribute to reducing poverty levels in North Sumatra.